The Role of Altruism in Strengthening Collaborative Academic Supervision in Educational Institutions - Sugesti, Tutik; Siregar, Astri Novia (Lembaga Riset Mutiara Akbar, 2025)
This study aims to analyze the role of altruism in strengthening collaborative academic supervision in educational institutions. Altruism, as an attitude of selfless help, is believed to contribute to a harmonious climate of cooperation between educators and leaders in academic supervision activities. This study uses a qualitative approach with a case study method at Madrasah Aliyah Persiapan Negeri 4 Medan. Data collection techniques were carried out through observation, in-depth interviews, and documentation. The results of the study indicate that altruism can strengthen interpersonal relationships, increase openness of communication, and encourage active participation in collaborative academic supervision. In addition, altruistic values have been shown to increase mutual trust and create a more open dialogue space between teachers and school management. Academic supervision based on strong social relationships and empathy also facilitates the process of identifying problems and finding joint solutions. The implication of this study is the importance of fostering altruistic values in the professional development of teachers and madrasah principals to create a supportive and productive work culture. This value should be integrated into leadership and supervision training in order to create a more humanistic, inclusive, and collaborative education system